2018
DOI: 10.1021/acs.orglett.8b02196
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Triggered C–C and C–N Bond Formation by C–S Bond Cleavage of Benzylic Thioethers

Abstract: The cleavage of sulfidic C-S bonds under visible-light irradiation was harnessed to generate carbocations under neutral conditions and synthesize valuable di- and triarylalkanes as well as benzyl amines. To this end, photoredox catalysis and direct photoinduced C-S bond cleavage are used as complementary approaches and participate in the versatility of the general strategy. Extensive mechanistic studies have demonstrated the diversity of the reaction mechanism at work in these different reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…Cr(ddpd) 2 BF 4 has been described in the same context, as have been Rose Bengal and Ru(bpy) 3 2+ . The latter compound was recently reported in a thioether activation through singlet oxygen …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cr(ddpd) 2 BF 4 has been described in the same context, as have been Rose Bengal and Ru(bpy) 3 2+ . The latter compound was recently reported in a thioether activation through singlet oxygen …”
Section: Resultsmentioning
confidence: 94%
“…It should be noted that the ability of photogenerated singlet oxygen to oxidize organic sulfides has also been reported . A recent example of such a reaction is the C–S bond cleavage of thioethers by Ru(bpy) 3 2+ ‐generated 1 O 2 . Based on these reports, an alternative mechanism for the formation of glycosyl cation 18 , which proceeds through radical intermediates, can be conceived.…”
Section: Resultsmentioning
confidence: 97%
“…Ar ange of benzyl sulfidesw eres ynthesized and tested in the reactionc onditions, as the benzylic position was expected to be easier to oxidize as recently reported by Masson and co-workers. [22] In this case, the amount of sulfide could be reduced to 5equiv with no loss in reactivity,w hile using CH 2 Cl 2 as the solvent. [20] Unfortunately,f urtherr eduction of the amount of the thioether led to diminished yields.…”
Section: Resultsmentioning
confidence: 99%
“…In their report, molecular iodine both acted as a photocatalyst for singlet oxygen generation and as a π‐Lewis acid. Recently, Masson and coworkers showed that benzylic thioethers can be oxidized to the radical cations through a combination of Ru(bpy) 3 (PF 6 ) 2 and molecular oxygen . Notably, this report revealed that singlet oxygen cleaves C−S bonds through oxidation.…”
Section: Methodsmentioning
confidence: 87%